2013
DOI: 10.1038/sc.2013.87
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spinal cord injuries without radiographic evidence of trauma: a prospective study

Abstract: Study design: Prospective study. Objectives: In a prospective study, 45 consecutive cases of cervical spinal cord injury without radiographic evidence of trauma (SCIWORET) who were treated non-operatively were analyzed to correlate the magnetic resonance image findings with the initial neurological deficit and the extent of neurological recovery at 2 years. Setting: University tertiary-care teaching hospital in South India. Methods: The neurological status of patients who did not have any radiographic or compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…Extraneural findings were disc herniation, ligamentum flavum bulging, prevertebral soft tissue swelling, or ligamentous abnormalities [ 33 ]. There is evidence in the literature suggesting that SCIWORA patients with no detectable MRI abnormalities usually have a better prognosis and recovery rate than the patients with MRI abnormalities [ 34 , 35 ].…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Extraneural findings were disc herniation, ligamentum flavum bulging, prevertebral soft tissue swelling, or ligamentous abnormalities [ 33 ]. There is evidence in the literature suggesting that SCIWORA patients with no detectable MRI abnormalities usually have a better prognosis and recovery rate than the patients with MRI abnormalities [ 34 , 35 ].…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…At three-month follow-up, a decision as to whether the patient should have another MRI is made on an individual basis. Although the latter is the most widely accepted immobilization protocol, some authors suggest using halter traction with a minimal weight for the first three weeks and immobilization in an extended cervical collar until three months after the injury [ 35 ]. Interestingly, Bosch et al [ 40 ] reported 21 patients with recurrent SCIWORA; 14 of them sustained their repeat episode while still wearing a rigid type of cervical brace.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a correlation between neurological outcome and MRI pattern has been described previously, 4,5,[11][12][13][14][15][16][17][18] this finding could not be confirmed by others. 2 The present study reports the existence of a relation between imaging type and neurological outcome in adult patients with SCIWORA.…”
Section: Discussionmentioning
confidence: 67%
“…Causes such as comorbid diseases affect the outcome. Pathogenesis, incidence, and outcome vary among different age groups because of anatomical and biomechanical differences [1,[3][4][5][6][7]. Previous studies have limited data concerning the clinical prognosis of SCIWORA because of the rarity of the disease in adults, especially in geriatric patients.…”
Section: Introductionmentioning
confidence: 99%